2024
DOI: 10.3390/ijms25052912
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Sepsis: A Focus on Cardiac Pathology

Giuseppe Bertozzi,
Michela Ferrara,
Aldo Di Fazio
et al.

Abstract: This study aims to analyze post-mortem human cardiac specimens, to verify and evaluate the existence or extent of oxidative stress in subjects whose cause of death has been traced to sepsis, through immunohistological oxidative/nitrosative stress markers. Indeed, in the present study, i-NOS, NOX2, and nitrotyrosine markers were higher expressed in the septic death group when compared to the control group, associated with also a significant increase in 8-OHdG, highlighting the pivotal role of oxidative stress i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 81 publications
(93 reference statements)
0
5
0
Order By: Relevance
“…This is primarily attributed to the tumor itself [1][2][3] or treatments such as chemotherapy 4 and surgery, which can compromise cardiac reserve function. Factors such as the high risk of infection 5,6 , electrolyte disturbances, stressors, anemia 7,8 , and frequent transfusions of various blood products during the bone marrow suppression period can all contribute to increased cardiac loading and consequently trigger acute cardiac dysfunction. Therefore, in the diagnosis and treatment of pediatric solid tumor patients, particular attention should be paid to cardiac function during the bone marrow suppression period.…”
Section: Discussionmentioning
confidence: 99%
“…This is primarily attributed to the tumor itself [1][2][3] or treatments such as chemotherapy 4 and surgery, which can compromise cardiac reserve function. Factors such as the high risk of infection 5,6 , electrolyte disturbances, stressors, anemia 7,8 , and frequent transfusions of various blood products during the bone marrow suppression period can all contribute to increased cardiac loading and consequently trigger acute cardiac dysfunction. Therefore, in the diagnosis and treatment of pediatric solid tumor patients, particular attention should be paid to cardiac function during the bone marrow suppression period.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ROS disrupt endothelial cell function, causing increased vascular permeability ( 102 ). This allows inflammatory cells and fluid to enter tissues, leading to edema and organ dysfunction ( 103 , 104 ). Oxidative stress also affects immune cell function and responsiveness, impairing their ability to clear pathogens.…”
Section: Sirts and Pathophysiology Of Sepsismentioning
confidence: 99%
“…Epidemiological studies have identified correlations between cardiovascular disease and the levels of 3-nitrotyrosine (NT), a marker of nitrosative stress, and asymmetric dimethylarginine (ADMA), an endogenous inhibitor of NO synthase [76,92,93]. NT is a marker of nitrosative stress resulting from the nitration process, affecting tyrosine residues in plasma proteins and atherosclerotic lesions.…”
Section: Nitrotyrosinementioning
confidence: 99%
“…ADMA serves as an endogenous inhibitor of NO synthase, leading to enzyme uncoupling and subsequent peroxynitrite production, thereby inducing nitrosative stress in vascular endothelial and smooth muscle cells [76,92]. Oxidative and nitrosative stress can trigger immune responses and inflammasome activation, exacerbating inflammation and contributing to cardiovascular disease progression [92,93]. Ferlazzo et al evaluated the inflammatory status by analyzing the transcription levels of inflammasome-associated genes in peripheral blood mononuclear cells (PBMCs) from recruited subjects.…”
Section: Nitrotyrosinementioning
confidence: 99%
See 1 more Smart Citation